ENGLISH PROFICIENCY OF HOTEL FRONT-LINERS: WHAT AND WHY? - Yerly A. Datu (Politeknik Ubaya, 2019)
English proficiency for hotel front-liners is paramount in giving excellent service for the guests. 60 seconds in the beginning of interaction leave the first impression for them. Therefore, oral communication skills play a significant role as a part of a must have competence for front-liners. This study was triggered by initial findings at some hotels in Surabaya where there was a discrepancy between hotel leaders’ perception and real English proficiency of their front-liners. The hotel leaders perceived lower than the passing grade of the hotel and urgency of upgrading their competence emerged. Two research questions should be answered: (1) WHAT level of the front liners’ English proficiency was, and (2) WHY they experienced difficulty when facing foreign guests. To answer the questions, a descriptive qualitative research employing a case study approach was conducted. The 3-star hotel consisting 20 participants was involved. Test of Business English Communication Competence Version 2.0 (TBECCv.2.0) was given to participants. TBECCv.20 was an ESP test created and developed for front-liners. After running the test, an online questionnaire was disseminated and interviews were also conducted for triangulation. Results revealed that the score range of 50-59 received the highest percentage; 40% which showed their English proficiency needed to be upgraded. Reasons of difficulty handling the foreign guests were due to (1) L1 interference, (2) educational background, (3) less English exposure, (4) the absence of ESP test at recruitment process. The study recommended further study for other categories of hotel and the staff professional development was recommended as well.